The Role of FGF19 and MALRD1 in Enterohepatic Bile Acid Signaling - Wang, Linda X.; Frey, Mark R.; Kohli, Rohit (Frontiers in Endocrinology, 2022)
Bile acids are the catabolic end products of cholesterol metabolism that are best known for their role in the digestion of lipids. In the last two decades, extensive investigation has shown bile acids to be important signaling molecules in metabolic processes throughout the body. Bile acids are ligands that can bind to several receptors. These include the nuclear receptor farnesoid X receptor (FXR) in ileal enterocytes. FXR activation induces the expression of fibroblast growth factor (FGF) 15/19, a hormone that can modulate bile acid levels, repress gluconeogenesis and lipogenesis, and promote glycogen synthesis. Recent studies have described a novel intestinal protein, MALRD1, that influences FGF15/19 levels. This signaling pathway presents an exciting target for treating metabolic disease and bile acid-related disorders.